Design of linear dynamic range and high sensitivity matrix quadrant APDs ROIC for position sensitive detector application. (May 2017) - Zheng, Hao; Ma, Rui; Zhu, Zhangming
Abstract: This paper presents a readout integrated circuits (ROIC) design for matrix quadrant APDs in position sensitive detector application, which eliminates three of the most important limits of the classical four-quadrant detectors: measurement range, dynamic range and sensitivity. The programmable gain control technique and low noise design technique were applied to widen linear dynamic range and increase the sensitivity in the proposed ROIC, respectively. In addition, the proposed ROIC with 32×32 receiver channels can track and position the incident light spot electrically and automatically within the active area of the APDs, supply four channels analog voltage output in parallel and output corresponding light spot position code in serial. The circuit is designed in a 0.18 µm CMOS process. The ROIC achieves a high gain of 106 dB Ω, a wide linear output swing of about 1 V, an input referred noise current of 1.95 pA/ Hz and a minimum detectable signal of 0.5 μA at SNR=3.3, leading to a linear dynamic range of 1:10, 000 with a 3.3 V power supply. The area of the ROIC chip is equal to 13×13 mm 2 .